Proposed Implementation of Lean Construction in Project Management Procedures in the Preparation of Project Work Plans (A Case Study of PT ICC TBK.) - Rifki Rahmadian Pangestu; Gatot Yudoko (Green Publisher Indonesia, 2026)
This study proposes the integration of Lean Construction principles into the Project Work Plan (RKP) procedure of PT ICC (Persero) Tbk to enhance project efficiency and minimize waste. Despite having a comprehensive project management framework based on PMBOK, inefficiencies persist in PT ICC’s operations due to reactive, administratively driven planning practices. Using a mixed-method approach—combining process mapping, in-depth interviews, expert judgment, and quantitative analysis through the Relative Importance Index (RII) and Spearman correlation—this research identifies key sources of waste, including waiting, overproduction, inventory, and underutilized talent. The study develops a revised RKP framework that integrates Lean tools such as the Last Planner System (LPS), Pull Planning, and Just-in-Time (JIT) procurement synchronization. Findings indicate that the implementation of Lean Construction can potentially improve time efficiency by up to 20% and reduce material waste by over 10%, while enhancing collaboration and workflow predictability. However, successful adoption requires cultural transformation supported by strong leadership commitment, practical training, and sustained change management efforts.